1990
DOI: 10.3109/03790799009166264
|View full text |Cite
|
Sign up to set email alerts
|

Outcome following physical trauma: a comparative approach

Abstract: This study aimed to examine physical and psychosocial changes after injury in a range of trauma patients. Three groups were selected for comparison purposes: severely head-injured patients, patients with major trauma, and those with minor trauma (n = 102). Outcomes were assessed by questionnaires and inventories administered to a family member or friend of the trauma survivor, approximately 1 year post-injury. Severely head-injured patients were reported to have the greatest degree of difficulty in self-care a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

1992
1992
2004
2004

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…Both CIQ and SEI were significantly rzlated to type of disability. The physical (non-pain) or sensory group reported significantly higher CIQ and SEI scores than the acquired brain injury group, which is consistent with previous research (Lyle et al, 1991;Stambmk et al, 1991). For the psychiatric and the chronic pain groups, however, a different trend was evident.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Both CIQ and SEI were significantly rzlated to type of disability. The physical (non-pain) or sensory group reported significantly higher CIQ and SEI scores than the acquired brain injury group, which is consistent with previous research (Lyle et al, 1991;Stambmk et al, 1991). For the psychiatric and the chronic pain groups, however, a different trend was evident.…”
Section: Discussionsupporting
confidence: 90%
“…The present study included persons with a range of disabilities, since it was anticipated that community integration would differ among disability groups. For example, previous studies (Lyle, Quine. Pierce, & Thomson, 1991;Stambrook et al, 1991) reported greater problems of psychosocial adjustment among persons with traumatic brain injuries than among those with physical disabilities.…”
mentioning
confidence: 99%
“…To identify how mobility outcome is currently measured after TBI, article titles and abstracts from the following electronic databases were searched from 1990 onwards: MEDLINE (1990through May 2004, CINAHL (1990through May 2004, EMBASE (1990through May 2004, and PsychLit (1990( through May 2004.…”
Section: Methodsmentioning
confidence: 99%
“…Few descriptive epidemiological studies of injury include a consideration of the natural history of injury recovery, nor have there been any specific attempts to quantify the epidemiology of injury-related morbidity and disability in the community. The need, however, for further research into the long-term outcomes of trauma in the community has been noted (Lyle et al 1990). The followup studies of injury in Australia are essentially confined to hospital case series for the purposes of evaluating and aiding clinical management, ( eg Day et al 1994) though rare exceptions to this _ rule can be found (eg Balla et al 1970).…”
Section: Australiamentioning
confidence: 99%